1984
DOI: 10.1111/j.1600-0676.1984.tb00952.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of jaundice: a pocket diagnostic chart

Abstract: ABSTRACT— Based on extensive clinical and clinical chemical information (107 different items) from 1002 jaundiced patients, we developed a diagnostic algorithm which was evaluated on a test sample of another 110 jaundiced patients. A primary classification into categories of obstructive jaundice (probability of obstruction ≥0.80), non‐obstructive jaundice (probability of obstruction ≤0.20), and of doubtful causes of jaundice (probability of obstruction: 0.20–0.80) was attempted. Among 234 patients in the data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…Less common causes include benign strictures, chronic pancreatitis, metastatic nodes to the porta hepatis, and primary sclerosing cholangitis. Many studies have shown that clinical data such as history, physical examination, and laboratory tests can accurately identify up to 90% of patients whose jaundice is caused by extrahepatic obstruction 1–21. However, complete assessment of extrahepatic obstruction often requires the use of various imaging modalities to confirm the presence, level, and cause of obstruction, and to aid in treatment planning.…”
Section: Introductionmentioning
confidence: 99%
“…Less common causes include benign strictures, chronic pancreatitis, metastatic nodes to the porta hepatis, and primary sclerosing cholangitis. Many studies have shown that clinical data such as history, physical examination, and laboratory tests can accurately identify up to 90% of patients whose jaundice is caused by extrahepatic obstruction 1–21. However, complete assessment of extrahepatic obstruction often requires the use of various imaging modalities to confirm the presence, level, and cause of obstruction, and to aid in treatment planning.…”
Section: Introductionmentioning
confidence: 99%
“…Differences Using Bayes' theorem and logistic discrimination an algorithm was developed for differentiating between four diagnostic groups: acute non-obstructive (medical) jaundice, chronic non-obstructive jaundice, benign obstructive (surgical) jaundice and malignant obstructive jaundice. The details of the algorithm have been reported previously (6). It takes into account 21 items of information from the history, physical examination and routine laboratory procedures ( Fig.…”
Section: Accepted For Publication I October I986mentioning
confidence: 99%
“…Καλά αποτελέσματα έχουν αναφερθεί και για συστήματα τα οποία χρησιμοποιούνται για την πρόγνωση της οξείας παγκρεατίτιδας καιρούς έχουν δημοσιευθεί αλγοριθμικοί πίνακες με σκοπό τη συστηματική και αποτελεσματική εφαρμογή των διαγνωστικών μέσων και τη διευκόλυνση της πορείας προς τη διάγνωση της αιτίας του ικτέρου [136][137][138][139][140][141][142][143][144][145][146]. Πρέπει να σημειωθεί όμως, ότι με την εισαγωγή νέων διαγνωστικών μεθόδων, οι αλγοριθμικοί πίνακες υφίστανται συνεχείς τροποποιήσεις.Επίσης, ένας τέτοιος πίνακας δεν έχει εφαρμογή σε όλους τους ασθενείς.…”
unclassified